Geological, Mineralogical, and Alteration Insights of the Intermediate-Sulfidation Epithermal Mineralization in the Sidi Aissa District, Northern Tunisia - Jamel Ayari; Maurizio Barbieri; Tiziano Boschetti; Ahmed Sellami; Paolo Ballirano; Abdelkarim Charef (Geosciences, 2025)
The Sidi Aissa Pb-Zn-(Ag) District, located within the Nappe Zone of northern Tunisia, has been reinterpreted as a typical intermediate-sulfidation (IS) epithermal mineralization system based on field observations and lithogeochemical analyses. Previously described as vein-style Pb-Zn deposits, the local geological framework is dominated by extensional normal faults forming half-grabens. These faults facilitated the exhumation of deep Triassic autochthonous rocks and the extrusion of 8-Ma rhyodacites and Messinian basalts. These structures, functioning as pathways for magmatic-hydrothermal fluids, facilitated the upward migration of acidic fluids, which interacted with the surrounding wall rocks, forming a subsurface alteration zone. The mineralization, shaped by Miocene extensional tectonics and magmatic activity, occurred in three stages: early quartz-dominated veins, an intermediate barite-rich phase, and late-stage supergene oxidation. Hydrothermal alteration, characterized by silicification, argillic, and propylitic zones, is closely associated with the deposition of base metals (Pb, Zn) and silver. The mineral assemblage, including barite, galena, sphalerite, and quartz, reflects dynamic processes such as fluid boiling, mixing, and pressure changes.